Leptin resistance: underlying mechanisms and diagnosis - Gruzdeva O (Dove Medical Press, 2019)
Olga Gruzdeva,1,2 Daria Borodkina,3 Evgenya Uchasova,1 Yulia Dyleva,1 Olga Barbarash1,2 1Federal State Budgetary Institution, Research Institute for Complex Issues of Cardiovascular Diseases, Kemerovo, Russian Federation; 2Federal State Budget Educational Institution of Higher Education, Kemerovo State Medical University of the Ministry of Healthcare of the Russian Federation, Kemerovo, Russian Federation; 3Autonomous Public Healthcare Institution of the Kemrovo Region, Kemerovo Regional Clinical Hospital Named After S.V. Beliyaev, Regional Center for Diabetes, Kemerovo, Russian Federation Abstract: Leptin and its receptors have been identified as key regulators of body weight and energy homeostasis. A decrease in tissue sensitivity to leptin leads to the development of obesity and metabolic disorders, such as insulin resistance and dyslipidemia. Mechanisms underlying the development of leptin resistance include mutations in the genes encoding leptin and its receptors, as well as proteins involved in self-regulation of leptin synthesis and blood–brain barrier permeability. Leptin resistance encompasses a complex pathophysiological phenomenon with a number of potential research lines. In this review, we analyze the existing data on the methods used to diagnose leptin resistance. Keywords: leptin, leptin resistance, soluble leptin receptor